The TERENO‐Rur Hydrological Observatory: A Multiscale Multi‐Compartment Research Platform for the Advancement of Hydrological Science. Issue 1 (2nd July 2018) - Bogena, H.R.; Montzka, C.; Huisman, J.A.; Graf, A.; Schmidt, M.; Stockinger, M.; von Hebel, C.; Hendricks-Franssen, H.J.; van der Kruk, J.; Tappe, W.; Lücke, A.; Baatz, R.; et al.
Abstract : Core Ideas: We provide an overview of the TERENO‐Rur hydrological observatory. We present information on general physical characteristics of the Rur catchment. Ongoing interdisciplinary research aims to advance understanding of complex hydrological processes. We provide an overview of the Rur hydrological observatory, which is the main observational platform of the TERENO (TERrestrial ENvironmental Observatories) Eifel/Lower Rhine Valley Observatory. The Rur catchment area exhibits distinct gradients in altitude, climate, land use, soil properties, and geology. The Eifel National Park is situated in the southern part of the Rur catchment and serves as a reference site for the hydrological observatory. We present information on general physical characteristics of the Rur catchment and describe the main features of the multi‐scale and multi‐compartment monitoring framework. In addition, we also present some examples of the ongoing interdisciplinary research that aims to advance the understanding of complex hydrological processes and interactions within the Rur catchment.